2013
DOI: 10.1037/a0030750
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mild stress increases alcohol intake in mice with low dopamine D2 receptor levels.

Abstract: Alcohol use disorders emerge from a complex interaction between environmental and genetic factors. Stress and dopamine D2 receptor levels (DRD2) have been shown to play a central role in alcoholism. To better understand the interactions between DRD2 and stress in ethanol intake behavior, we subjected Drd2 wild-type (+/+), heterozygous (+/-), and knockout (-/-) mice to 4 weeks of chronic mild stress (CMS) and to an ethanol two-bottle choice during CMS weeks 2-4. Prior to and at the end of the experiment, the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 82 publications
7
34
0
Order By: Relevance
“…While, for example, high levels of enkephalins are associated with pain suppression and low serotonin levels with depression, an individual with the Taq1 A1 allele of the Dopamine Receptor Gene ( DRD2 ), lacks enough dopamine receptor sites to release the normal amount of dopamine into the Reward Center of the brain and dopamine function is reduced (Noble et al, 1991; Delis et al, 2013). Humans possessing the A1 variant crave and seek substances and behaviors known to cause dopamine release preferentially at the nucleus accumbens (NAc) in the meso-limbic system (Stice and Dagher, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While, for example, high levels of enkephalins are associated with pain suppression and low serotonin levels with depression, an individual with the Taq1 A1 allele of the Dopamine Receptor Gene ( DRD2 ), lacks enough dopamine receptor sites to release the normal amount of dopamine into the Reward Center of the brain and dopamine function is reduced (Noble et al, 1991; Delis et al, 2013). Humans possessing the A1 variant crave and seek substances and behaviors known to cause dopamine release preferentially at the nucleus accumbens (NAc) in the meso-limbic system (Stice and Dagher, 2010).…”
mentioning
confidence: 99%
“…They may become serious cocaine abusers or have unhealthy appetites, which lead to, eating disorders like obesity, overeating or at the other extreme, anorexia nervosa (AN), they also suffer from high levels of stress over an extended period of time. To activate their dopaminergic pathways, a self-healing process to offset their low D2 receptors, individuals are driven to engage in activities which will increase brain dopamine function (Noble et al, 1991, 1993; Delis et al, 2013). The consumption of alcohol in large quantities or carbohydrate binging stimulates the brain’s production of and utilization of dopamine (Blum et al, 1996, 2000).…”
mentioning
confidence: 99%
“…Along these lines Delis et al [25] observed that in the presence of a stressful environment, low DRD2 levels are associated with increased ethanol intake and preference and that under this condition, increased ethanol consumption could be used as a strategy to alleviate negative mood this also supports dopamine agonist therapy not antagonistic. Moreover, recent work by Willuhn et al [26] surprisingly found that phasic dopamine decreased in the ventral medium striatum (VSM) as the rate of cocaine intake increased, with the decrement in dopamine in the VMS significantly correlated with the rate of escalation.…”
Section: Introductionmentioning
confidence: 96%
“…It is our hypothesis that D2 receptor stimulation In fact, stress and dopamine D2 receptor levels play a significant role in alcohol seeking behaviors. Delis et al [39] observed that in the presence of a stressful environment, low DRD2 levels are associated with increased ethanol intake. Under this condition, increased ethanol consumption could be used as a strategy to alleviate negative mood, which further supports dopamine agonist therapy.…”
Section: Support For Reward Deficiency Syndrome (Rds) As the "True Phmentioning
confidence: 99%